MEASURING THE PRODUCTIVITY OF ISLAMIC BANKS' PERFORMANCE WITH STOCHASTIC FRONTIER MEASURES: EMPIRICAL EVIDENCE IN INDONESIA - Wahyudi, Syachrul; Siregar, Saparuddin; Nurhayati, Nurhayati; Konadi, Win (Universitas Padjadjaran, 2024)
This research investigates the effect of non-financial objectives on Islamic bank efficiency. The sample data are taken from Islamic banks in Indonesia, spanning 2008-2020. By using the parametric approach, the Stochastic Frontier Analysis (SFA) method is employed to estimate the maximum likelihood and profit efficiency level. The model used in this research is called the BC’95 model in translog form. The input-output variables in this research are chosen based on the intermediation approach. The results show that publicity and zakat have positive and significant effects on the efficiency level of Islamic banks in Indonesia. On the contrary, the qardhul hasan has a negative but significant effect. In this case, zakat has the strongest sensitivity toward the dependent variable. Overall, the efficiency trend is in line with national and global macroeconomic conditions, and it strengthens the existence of non-financial objectives in the Islamic bank's efficiency measurement model. It is hoped that this research can be a gateway for regulators, practitioners, and academics to continue to explore and encourage strengthening the manifestation of Islamic values in Islamic bank operational practices.